Cross-Addiction Risk Profile Associations with COVID-19 Anxiety: a Preliminary Exploratory Study. - Dowd, Brendan; Hein, Kaiden; Diez, Stephanie L.; Prokofieva, Maria; Kannis-Dymand, Lee; Stavropoulos, Vasileios (International Journal of Mental Health & Addiction, 2024)
"Cross-addiction" involves a person substituting one form of addictive behaviour for another. Indeed, cross-additive presentations have been frequently described (e.g. from drugs to alcohol, gambling to sex), and risk profiles have been assumed. Nevertheless, there has been a dearth of evidence considering the occurrence of cross-addiction risk profiles in the community. This research is imperative for informing effective prevention/intervention policies, especially under anxiety-provoking conditions, such as the current coronavirus pandemic. To address this need, a cross-sectional exploratory research design was utilized, with quantitative survey data obtained from 968 respondents (18–64; M = 29.5 years, SD = 9.36), who completed an online survey regarding a range of addictive behaviours (i.e. abuse of alcohol, drug, smoking, online gaming, shopping, internet, exercise, online gambling, sex, and social media) and their anxiety about the coronavirus. Latent class/profiling analyses were implemented to (a) explore profiles of cross-addiction risk, (b) describe the characteristics and the proportions of these profiles, and (c) identify their differential associations with the pandemic precipitated anxiety. Findings revealed two distinct profiles/types, the "cross-addiction low risk" (57.4%) and the "cross-addiction high risk" (42.6%). Those in the latter scored consistently higher across all behaviours assessed, were more likely to suffer from concurrent addictive problems, and reported significantly higher levels of pandemic-related anxiety. Implications for prevention, assessment, and treatment and future research are discussed.